Interrogating postfeminism : gender and the politics of popular culture - Tasker, Yvonne, 1964-; Negra, Diane, 1966- (Console-ing passions : television and cultural power, 2007)
Brings feminist critique to bear on contemporary "postfeminist" mass media culture, analyzing phenomena ranging from female action films to the "girling" of aging women in productions such as the movie Something's Gotta Give and the British television series 10 Years Younger.